ANALISIS PERBANDINGAN LAJU INFLASI KOTA MANADO DAN PERDESAAN DI SULAWESI UTARA - Norma O. F. Regar; Caroline B.D. Pakasi; Grace A.J. Rumagit (Universitas Sam Ratulangi, 2015)
ABSTRACT The problems of the reseach are how the description and comparison of the inflation rate in the city of Manado and rural areas in North Sulawesi, and how the influence of the inflation rate of each expenditure to the general inflation rate in the city and rural areas. The research was conducted in the city of Manado North Sulawesi for 3 (three) months. The data used is inflation data from January 2009 to December 2014, which analyzed qualitative, and quantitative descriptive in the statistical analysis using different test average analysis and multiple linear regression. The results showed that the average inflation rate for rural areas is relatively high compared with urban areas. seven groups of grouping expenditure in the inflation calculation period 2009-2014 showed that there are four groups that the inflation average rate is higher in cities than in rural, which includes foodstuffs, housing, electricity, gas and fuel; education, recreation and sports; and group transport, communications and financial services. The rest, three other groups show the average inflation rate in the city is lower than in rural areas, which include: food, beverages, cigarettes and tobacco; clothing; and health groups. The inflation rate in the city of Manado produce the same patterns with the rate of inflation in the rural areas. The rate of general inflation both in the city of Manado and rural areas is strongly influenced by the inflation rate of seven groups of expenditure for goods and services which consist of foodstuffs, food, clothing, housing, health, education and transport. Keyword : Inflation Rate, Expenditure Groups.